Journal for the Study of Judaism in the Persian, Hellenistic, and Roman Period (JSTOR)
The Journal for the Study of Judaism is a leading international forum for scholarly discussions on the history, literature and religious ideas on Judaism in the Persian, Hellenistic and Roman period. It provides biblical scholars, students of rabbinic literature, classicists and historians with essential information. Since 1970 the Journal for Study of Judaism has been securing its position as one of the world?s leading journals.
Keywords: Jewish Studies